Topological Data Analysis of C. elegans Locomotion and Behavior - Thomas, Ashleigh; Bates, Kathleen; Elchesen, Alex; Hartsock, Iryna; Lu, Hang; Bubenik, Peter (Frontiers in Artificial Intelligence, 2021)
We apply topological data analysis to the behavior of C. elegans, a widely studied model organism in biology. In particular, we use topology to produce a quantitative summary of complex behavior which may be applied to high-throughput data. Our methods allow us to distinguish and classify videos from various environmental conditions and we analyze the trade-off between accuracy and interpretability. Furthermore, we present a novel technique for visualizing the outputs of our analysis in terms of the input. Specifically, we use representative cycles of persistent homology to produce synthetic videos of stereotypical behaviors.